TGFβ is a master regulator of radiation therapy-induced anti-tumor immunity - Vanpouille-Box, Claire (Cancer Res, 2015)
T cells directed to endogenous tumor antigens are powerful mediators of tumor regression. Recent immunotherapy advances have identified effective interventions to unleash tumor-specific T cell activity in patients who naturally develop them. Eliciting T cell responses to a patient's individual tumor remains a major challenge. Radiation therapy can induce immune responses to model antigens expressed by tumors, but it remains unclear if it can effectively prime T cells specific for endogenous antigens expressed by poorly immunogenic tumors. We hypothesized that TGFβ activity is a major obstacle hindering the ability of radiation to generate an in situ tumor vaccine. Here we show that antibody-mediated TGFβ neutralization during radiation therapy effectively generates CD8(+) T cell responses to multiple endogenous tumor antigens in poorly immunogenic mouse carcinomas. Generated T cells were effective at causing regression of irradiated tumors and non-irradiated lung metastases or synchronous tumors (abscopal effect). Gene signatures associated with IFNγ and immune-mediated rejection were detected in tumors treated with radiation therapy and TGFβ blockade in combination but not as single agents. Upregulation of programmed death (PD) ligand-1 and -2 in neoplastic and myeloid cells and PD-1 on intratumoral T cells limited tumor rejection resulting in rapid recurrence. Addition of anti-PD-1 antibodies extended survival achieved with radiation and TGFβ blockade. Thus, TGFβ is a fundamental regulator of radiation therapy ability to generate an in situ tumor vaccine. The combination of local radiation therapy with TGFβ neutralization offers a novel individualized strategy for vaccinating patients against their tumors.